The Degree of Branching of Serum IgG N-glycans as a Marker of Advanced Endometriosis - Ewa Maria Kratz; Katarzyna Sołkiewicz; Marcin Jędryka (Molecules)
Endometriosis is a gynecological disease for which the diagnostics are difficult and often invasive; therefore, non-invasive diagnostic methods using sensitive and specific parameters present in easily available body fluid such as blood serum are needed for the detection of this disease. Our study aimed to answer the question of whether there are any differences between women with advanced endometriosis (AE), patients with gynecological diseases other than endometriosis (NE), and healthy women (control) in terms of the number of antennas of N-glycans from serum IgG. The degree of branching of IgG N-glycans was determined by a modified lectin ELISA with biotinylated lectin Con A (Canavalia ensiformis agglutinin) recognizing α-linked mannose, specifically reacting with biantennary N-glycans. The PHA-L/Con A ratio was calculated from the obtained N-glycan reactivities with Con A and PHA-L (Phaseolus vulgaris leucoagglutinin, specific to tri- and/or tetra-antennary N-linked glycans). The expression of Con A-reactive biantennary N-glycans in serum IgG was significantly lower in the control group than in the NE group (p = 0.045). The values of the PHA-L/Con A ratio were significantly higher in the NE group than in the AE and control groups (p = 0.019 and p = 0.022, respectively). The PHA-L/Con A ratio could be taken into account as a parameter helpful in the non-invasive diagnosis of advanced endometriosis, thus differentiating this disease from other gynecological diseases with an inflammatory background.